Multiple myeloma masquerading as ascites: a rare case report - Priyadarshi, B. P.; Singh, Mahendra; Verma, Ashok K.; Kaushik, Rishibha (International Journal of Advances in Medicine, 2025)
A 45-year-old woman with progressive abdominal distension was diagnosed with multiple myeloma after presenting with unexplained ascites. Investigations revealed anemia, hypercalcemia, renal dysfunction, lytic bone lesions, and 62% atypical plasma cells in bone marrow. Liver biopsy showed amyloid deposition, suggesting amyloidosis-induced hepatic dysfunction as the cause of ascites. Other causes, including portal hypertension and malignancy, were ruled out. Myelomatous ascites is rare and requires high suspicion for diagnosis. This case highlights the importance of considering multiple myeloma in unexplained ascites, as early recognition and treatment can significantly improve patient outcomes.